Ammonia-modified graphene sheets decorated with magnetic Fe3O4 nanoparticles for the photocatalytic and photo-Fenton degradation of phenolic compounds under sunlight irradiation - Boruah, Purna K.; Sharma, Bhagyasmeeta; Karbhal, Indrapal; Shelke, Manjusha V.; Das, Manash R. (Journal of hazardous materials, 2017)
Synthesis of easily separable and eco-friendly efficient catalyst with both photocatalytic and photo-Fenton degradation properties is of great importance for environment remediation application. Herein, ammonia-modified graphene (AG) sheets decorated with Fe3O4 nanoparticles (AG/Fe3O4) as a magnetically recoverable photocatalyst by a simple in situ solution chemistry approach. First, we have functionalized graphene oxide (GO) sheets by amide functional group and then Fe3O4 nanoparticles (NPs) are doped onto the functionalized GO surface. The AG/Fe3O4 nanocomposite showed efficient photocatalytic activity towards degradation of phenol (92.43%), 2-nitrophenol (2-NP) (98%) and 2-chlorophenol (2-CP) (97.15%) within 70–120 min. Consequently, in case of photo-Fenton degradation phenomenon, 93.56% phenol, 98.76% 2-NP and 98.06% of 2-CP degradation were achieved within 50–80 min using AG/Fe3O4 nanocomposite under sunlight irradiation. The synergistic effect between amide functionalized graphene and Fe3O4 nanoparticles (NPs) enhances the photocatalytic activity by preventing the recombination rate of electron-hole-pair in Fe3O4 NPs. Furthermore, the remarkable reusability of the AG/Fe3O4 nanocomposite was observed up to ten cycles during the photocatalytic degradation of these phenolic compounds.

Atomically dispersed manganese on graphene nanosheets as biocompatible nanozyme for glutathione detection in liver tissue lysate using microfluidic paper-based analytical devices - Baruah, Diksha J.; Thakur, Ashutosh; Roy, Esha; Roy, Kallol; Basak, Sumanjita; Neog, Dipankar; Bora, Himangsu K.; Konwar, Rituraj; Chaturvedi, Vikash; Shelke, Manjusha V.; Das, Manash R. (ACS Applied Materials & Interfaces, 2023)
Recently, single atom catalysts (SACs) featuring M-N-x (M = metal) active sites on carbon support have drawn considerable attention due to their promising enzyme-like catalytic properties. However, typical synthesis methods of SACs often involve energy-intensive carbonization processes. Herein, we report a facile one-pot, low-temperature, wet impregnation method to fully utilize M-N-4 sites of manganese phthalocyanine (MnPc) by decorating molecular MnPc over the sheets of graphene nanoplatelets (GNP). The synthesized MnPc@GNP exhibits remarkable peroxidase-mimic catalytic activity toward the oxidation of chromogenic 3,3 `,5,5(')-tetramethylbenzidine (TMB) substrate owing to the efficient utilization of atomically dispersed Mn and the high surface-to-volume ratio of the porous catalyst. A nanozyme-based colorimetric sensing probe is developed to detect important biomarker glutathione (GSH) within only 5 min in solution phase based on the ability of GSH to effectively inhibit the TMB oxidation. The high sensitivity and selectivity of the developed colorimetric assay enable us to quantitatively determine GSH concentration in different biological fluids. This work, for the first time, reports a rapid MnPc@GNP nanozyme-based colorimetric assay in the solid substrate by fabricating microfluidic paper-based analytical devices (mu PADs). GSH is successfully detected on the fabricated mu PADs coated with only 6.0 mu g of nanozyme containing 1.6 nmol of Mn in the linear range of 0.5-10 mu M with a limit of detection of 1.23 mu M. This work also demonstrates the quantitative detection of GSH in mice liver tissue lysate using mu PADs, which paves the way to develop mu PADs for point-of-care testing.
Keywords: colorimetricsensing; Glutathione; mu PADs; nanozyme; single atom catalyst; tissue lysate